Antiinflammatory and Antinociceptive Activities of Methanolic Extract of Leaves of Bischofia javanica Blume on Experimental Animals - LINGADURAI, SUTHARSON; KANT NATH, LILA; KUMAR KAR, PRASANNA; E. BESRA, SHILA; VEDASIROMANI JOSEPH, RAJAN (Asian Journal of Chemistry, 2010)
The methanolic extract of leaves of Bischofia javanica was screened (200, 400 and 600 mg/kg p.o) for antiinflammatory activity by acute carrageenan induced paw edema in rats, sub-chronic cotton pellet induced granuloma in rats and chronic study by Freund's adjuvant induced arthritis in rats. In all the three models of antinflammatory studies, 400 and 600 mg/kg of methanolic extract shows significant (p < 0.001 vs. control) effect. Antinociceptive screening by Writhing test and Tail immersion test supported both the peripheral and central mechanism behind pain relieving effect. This study had rationalised the ethno medicinal use of the plant for cut, burns and injury by tribal people of Sikkim.